2020
DOI: 10.1007/s00125-020-05123-6
|View full text |Cite
|
Sign up to set email alerts
|

A core outcome set for studies of gestational diabetes mellitus prevention and treatment

Abstract: Aims/hypothesis The aim of this systematic review was to develop core outcome sets (COSs) for trials evaluating interventions for the prevention or treatment of gestational diabetes mellitus (GDM). Methods We identified previously reported outcomes through a systematic review of the literature. These outcomes were presented to key stakeholders (including patient representatives, researchers and clinicians) for prioritisation using a three-round, e-Delphi study. A priori consensus criteria informed which outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 25 publications
2
44
1
Order By: Relevance
“…Preparation of this protocol is in line with the COS-STAP Statement recommendations which gives guidance on items considered essential in a COS protocol [27]. Our methodology is similar to previous work our group has carried out in development of COS in other areas of maternal diabetes [28][29][30].…”
Section: Methodsmentioning
confidence: 98%
“…Preparation of this protocol is in line with the COS-STAP Statement recommendations which gives guidance on items considered essential in a COS protocol [27]. Our methodology is similar to previous work our group has carried out in development of COS in other areas of maternal diabetes [28][29][30].…”
Section: Methodsmentioning
confidence: 98%
“…Of seven previously identified protocols, four had published a COS development study. (17)(18)(19)(20) Overall publications had increased in all areas of women's, newborn and neonatal health (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The variation in outcome reporting was considerable: for example, a review of intrauterine growth restriction trials identified 238 outcomes and a review of bladder pain syndrome trials identified only five. (46,58) Published core outcome sets Twenty completed COS development studies were identified (table S6) (17)(18)(19)(20)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) including: 13 (65%) in pregnancy and childbirth, 3 (15%) in newborn and neonatal health, 2 (10%) in benign gynaecology and subfertility and 2 (10%) in oncology. Sixteen studies (80%) were developed in an international context.…”
Section: Systematic Reviews Characterizing the Inconsistency In Outcomentioning
confidence: 99%
“…The committee also considered outcomes in the final core outcome set (COS) for GDM treatment research. 29 Reference to the COS for future GDM treatment research provided objective prioritisation of outcomes from a large international multidisciplinary group of relevant stakeholders. Finally, the committee considered all outcomes studied in the HAPO study, 5 the landmark international multicentre observational study that demonstrated associations between increasing levels of glucose levels on oral glucose tolerance testing and adverse pregnancy outcomes.…”
Section: Methods and Analysismentioning
confidence: 99%